PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, BESARNYA GAJI, DAN MOTIVASI MENGAJAR TERHADAP KINERJA GURU SEKOLAH DASAR WASKITO DI PAMULANG - Nurdin, Nurdin (MAJALAH ILMIAH WIDYA, 2012)
The headmaster needs to have good leadership in order to motivate teachers to apply their knowledge so that the learning-teaching process result can achieve its target.Â The objective of this paper is to know the influence of the leadership of the headmaster towards the teacherâs achievement and motivation. The method used observational and survey, which is conducted in Waskitoâs elementary school at Pamulang. The sample randomly taken. The result shows that the leadership and the wages do not directly influence the performance of the teacherâs.